2016
DOI: 10.1097/sla.0000000000001484
|View full text |Cite
|
Sign up to set email alerts
|

Features of Postoperative Immune Suppression Are Reversible With Interferon Gamma and Independent of Interleukin-6 Pathways

Abstract: ObjectiveTo evaluate the role of IL-6 pathways in post-operative immune-suppression and to assess the reversibility of this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 32 publications
(46 reference statements)
0
63
0
3
Order By: Relevance
“…It may a result of immune compromising effect led by anticancer treatments. [12][13][14] Noteworthy, this study showed that lung cancer was the most common cancer type (accounted for 22.4%), which may have higher susceptibility SARS-CoV-2 infection than other type cancers. There may be two main reasons: (1) lung cancer accounts for a large .…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It may a result of immune compromising effect led by anticancer treatments. [12][13][14] Noteworthy, this study showed that lung cancer was the most common cancer type (accounted for 22.4%), which may have higher susceptibility SARS-CoV-2 infection than other type cancers. There may be two main reasons: (1) lung cancer accounts for a large .…”
Section: Discussionmentioning
confidence: 76%
“…Besides, cancer patients with COVID-19 might have more complications due to their old age, weakened immune system and the side effects of undergoing treatments. 12,14 Therefore, we recommend systemic screening should be conducted among hospitalized cancer patients. In our study, we also observed that ongoing anticancer treatment was interrupted in most patients because of the diagnosis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The safety and management of cancer patients in the current SARS-CoV-2 outbreak is urgent and most cancer clinics need to establish a contingency plan. It is well established that cancer patients are more susceptible to infections because of the immunosuppressive state caused by both anticancer treatments and surgery [1][2][3]. A recent study from Prof He and colleagues shows that the risk of developing severe events in COVID-19 disease is statistically significant higher in patients with cancer, with a hazard ratio of 3.56 [4].…”
Section: All Authors Have Contributed Equallymentioning
confidence: 99%
“…3,4 Patients with cancer are more susceptible to infection than individuals without cancer because of their systemic immunosuppressive state caused by the malignancy and anticancer treat ments, such as chemotherapy or surgery. [5][6][7][8] Therefore, these patients might be at increased risk of COVID-19 and have a poorer prognosis.…”
mentioning
confidence: 99%